A successful booster umbilical cord blood transplantation for a 10-year-old patient with beta-thalassemia major in India - Vijay Ramanan (Wolters Kluwer Medknow Publications, 2021)
Beta-thalassemia major is characterized by a genetic deficiency in synthesis of beta-globin chains, resulting in reduced levels of functional hemoglobin. It is characterized by anemia, hepatosplenomegaly, and iron overload due to repeated blood transfusion. Hematopoietic stem cell transplantation is currently the only known curative treatment. We present a case of a 10-year-old girl with beta-thalassemia major who was successfully cured with allogeneic booster umbilical cord blood (UCB) transplantation with outcome data after 3 years of transplantation, in India. Postdiagnosis, she was on regular once-a-month blood transfusion until the age of 10 years, with no improvement. No serious adverse events occurred in the patient post-UCB transplantation. Chronic graft versus host disease was limited and was managed by medicines. Signs of primary graft rejection were also not seen.